PENGARUH MODEL PEMBELAJARAN OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA - Istiqomah Istiqomah; Hidayati Hidayati; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This research aims to determine the tendency of natural science result study between using Outdoor Learning model and Ekspository learning model. Comparatively aims to determine differences on natural science result study student class VII MTs N Dlingo on both the learning model. The data analysis technique using t-test but previously performed analysis prerequisite test including normality test distribution and homogeneity of variance test. The result of descriptive research showed that the tendency on natural science result study Outdoor Leraning model included the very high category, and the use of Ekspository learning model included the high category. The analysis shows that there are significant differences on natural science result study on both the learning model. The average of natural science result study using Outdoor Learning model is higher than EkspositoryÂ  learning model, so it can be concluded that the effect of Outdoor Learning model on natural science result study.